Mesenchymal stem cells and pulmonary fibrosis: a bibliometric and visualization analysis of literature published between 2002 and 2021 - Yang, Yanli; Chen, Yu; Liu, Yang; Ning, Zongdi; Zhang, Zhaoliang; Zhang, Yan; Xu, Ke; Zhang, Liyun (Frontiers in Pharmacology, 2023)
Introduction: Pulmonary fibrosis (PF) is a severe disease that can lead to respiratory failure and even death. However, currently there is no effective treatment available for patients with PF. Mesenchymal stem cells (MSCs) have been recently shown to have therapeutic potential for PF. We analyzed the literature focused of MSCs and PF to provide a comprehensive understanding of the relationship between MSCs and PF. Methods: We searched the Web of Science Core Collection database for literature from 2002 through 2021 that involved MSCs and PF. The included studies were then analyzed using CiteSpace and VOSviewers software. Results: A total of 1,457 studies were included for analysis. Our findings demonstrated the following: 1) an increasing trend of MSC and PF research; 2) among the 54 countries/regions of author affiliations, the United States was the most frequent, and the University of Michigan (n = 64, 2.8%) was the top institution; 3) Rojas Mauricio published the most articles and PLOS ONE had the most related studies; and 4) keywords, such as idiopathic pulmonary fibrosis, mesenchymal stem cells, and systemic sclerosis, were listed more than 100 times, indicating the research trend. Other common keywords, such as inflammation, myofibroblasts, fibroblasts, aging, telomerase or telomere, and extracellular matrix demonstrate research interests in the corresponding mechanisms.1) The number of publications focused on MSCs and PF research increased during the study period; 2) Among the 54 countries/regions of author affiliations, most articles were published in the United States of America, and the University of Michigan (n = 64, 2.8%) had the largest number of publications; 3) Rojas Mauricio published the most articles and PLOS ONE had the most related studies; 4) Keywords, such as idiopathic pulmonary fibrosis, MSCs, and systemic sclerosis, were listed more than 100 times, representing a research trend. Other common keywords included inflammation, myofibroblasts, fibroblasts, aging, telomerase or telomere, and extracellular matrix. Discussion: During the past 2 decades, MSCs have been proposed to play an important role in PF treatment. An increasing amount of literature focused on MSCs and PF research has been published. Our findings provide insight into the current status and research trends in the field of MSCs and PF research during the past 2 decades, which could help researchers understand necessary research directions. In the future, more preclinical and clinical studies should be conducted in this field to support the application of MSCs in the treatment of PF.